Perancangan Art Therapy Center dengan Pendekatan Biophilic Architecture di Gorontalo - Zulkifli Otaya; Heryati; Niniek Pratiwi (Transbahasa, 2025)
Mental health is a crucial aspect of individual and societal well-being. Poor mental health conditions can contribute to an increase in suicide cases. According to the Institute for Human and Ecological Studies (INHIDES, 2023), from January to June 2023, there were 17 suicide cases in Gorontalo Province, averaging 3–4 cases per month. Furthermore, data show that only 8% of people with mental disorders in Gorontalo receive adequate healthcare services. The high number of suicides and the low percentage of people with mental disorders receiving adequate healthcare highlight the urgent need for preventive mental health measures. This study emphasizes art therapy as an effective approach to addressing mental health issues by using art as a means of expression. A descriptive research method was employed to explain current symptoms, events, and phenomena. Data collection techniques included interviews, observations, documentation, literature review, and comparative studies. Data analysis was conducted descriptively to provide a comprehensive understanding of the issues studied. The proposed Art Therapy Center, designed with a Biophilic Architecture approach, is expected to serve as an innovative solution to support mental health services in Gorontalo, not only focusing on rehabilitation but also raising public awareness about the importance of mental health through integration with the natural environment.